Education – Determinant of Consumer's Conditions in an Era of Technological Change - Cristina Burghelea; Mirela Ionela Aceleanu (Amfiteatru Economic Journal, 2014)
In the era of technological change, consumers face an environment increasingly complex, leading to significant challenges regarding buying and consuming choices and consumer protection. The most important and most influential technological changes in terms of the impact on the consumer, are iduced by internet, digitization and globalization. However, the era of technological change also means developing biotechnologies, nanotechnologies, new materials and new energy sources, all these changing people's lives, living conditions, their needs and their behaviour as consumers.
Keywords: D11; D18; I21; 330; education; consumer education; lifelong learning; consumer behaviour; technological changes; protection of consumer rights; the new consumer; consumer condition index